Short-Term Effects of Elexacaftor/Tezacaftor/Ivacaftor Combination on Glucose Tolerance in Young People With Cystic Fibrosis-An Observational Pilot Study - Insa Korten; Elisabeth Kieninger; Linn Krueger; Marina Bullo; Christa E. Flück; Christa E. Flück; Philipp Latzin; Carmen Casaulta; Claudia Boettcher; Claudia Boettcher (Frontiers Media S.A., 2022)
BackgroundThe effect of elexacaftor/tezacaftor/ivacaftor (ELX/TEZ/IVA) on glucose tolerance and/or cystic-fibrosis-related diabetes (CFRD) is not well understood. We performed an observational study on the short-term effects of ELX/TEZ/IVA on glucose tolerance.MethodsSixteen adolescents with CF performed oral glucose tolerance tests (OGTT) before and 4-6 weeks after initiating ELX/TEZ/IVA therapy. A continuous glucose monitoring (CGM) system was used 3 days before until 7 days after starting ELX/TEZ/IVA treatment.ResultsOGTT categories improved after initiating ELX/TEZ/IVA therapy (p = 0.02). Glucose levels of OGTT improved at 60, 90, and 120 min (p < 0.05), whereas fasting glucose and CGM measures did not change.ConclusionShortly after initiating ELX/TEZ/IVA therapy, glucose tolerance measured by OGTT improved in people with CF. This pilot study indicates that ELX/TEZ/IVA treatment has beneficial effects on the endocrine pancreatic function and might prevent or at least postpone future CFRD.